2021
DOI: 10.1080/1828051x.2021.1955627
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium butyrate protects lipopolysaccharide-induced inflammatory response in lambs through inhibiting TLR4/NF-κB signalling pathway

Abstract: This study evaluated the effects of dietary coated sodium butyrate (CSB) on lipopolysaccharide (LPS)-induced inflammatory response in weaned lambs. A basal diet was supplemented with CSB at 0, 2 or 3 g/kg feed for 28 days and/or intraperitoneally injected with 100 lg/kg BW Escherichia coli LPS (0 g/kg CSB, 0 g/kg CSB and LPS, 2 g/kg CSB and LPS, 3 g/kg CSB and LPS). The results showed that CSB supplementation conferred significant protective effects against LPS-induced inflammatory response by reducing in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Sodium butyrate, a fatty acid salt, induces the functional maturation of intestinal epithelial cells by promoting their proliferation and inhibiting their apoptosis, thereby improving digestion and fostering intestinal mucosal development [ 27 , 28 , 29 ]. It has been reported that the supplementation of the diets of weaning piglets, calves, and lambs with an appropriate amount of butyrate can enhance their disease resistance, improve the intestinal microbiome, and increase growth performance [ 30 , 31 , 32 ]. In this study, we found that, in the weaned rabbits, dietary butyrate supplementation significantly increased the average daily feed intake and the average daily weight gain while reducing the rate of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate, a fatty acid salt, induces the functional maturation of intestinal epithelial cells by promoting their proliferation and inhibiting their apoptosis, thereby improving digestion and fostering intestinal mucosal development [ 27 , 28 , 29 ]. It has been reported that the supplementation of the diets of weaning piglets, calves, and lambs with an appropriate amount of butyrate can enhance their disease resistance, improve the intestinal microbiome, and increase growth performance [ 30 , 31 , 32 ]. In this study, we found that, in the weaned rabbits, dietary butyrate supplementation significantly increased the average daily feed intake and the average daily weight gain while reducing the rate of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The depth of crypt determines the speed of epithelial cell formation by mitosis of intestinal villi, and reflects the colonization rate and maturity of crypt cells. Therefore, the value of villus height/ crypt depth is an important index to measure intestinal development and function (17,18). In addition, some studies have shown that there is a positive correlation between villi length, nutrient absorption and digestibility.…”
Section: Effects Of Tea Polyphenols On Growth Performance and Intesti...mentioning
confidence: 99%